2019
DOI: 10.1038/s41567-019-0542-4
|View full text |Cite
|
Sign up to set email alerts
|

Lattice defects induce microtubule self-renewal

Abstract: Microtubules are dynamic polymers, which grow and shrink by addition and removal of tubulin dimers at their extremities. Within the microtubule shaft, dimers adopt a densely packed and highly ordered crystal-like lattice structure, which is generally not considered to be dynamic. Here we report that thermal forces are sufficient to remodel the microtubule shaft, despite its apparent stability. Our combined experimental data and numerical simulations on lattice dynamics and structure suggest that dimers can spo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 47 publications
4
70
0
Order By: Relevance
“…Fig. 1) or by kinesin-mediated disruption of the lattice 9,23,24 . Put another way, F-actin incorporation may occur in response to mechanical or structural stress 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 1) or by kinesin-mediated disruption of the lattice 9,23,24 . Put another way, F-actin incorporation may occur in response to mechanical or structural stress 25 .…”
Section: Discussionmentioning
confidence: 99%
“…We started by comparing the micropatterning efficiency of two proteins broadly used for micropatterning, NeutrAvidin 7,8,17 and Fibrinogen 11,18,19 . Except for figure 4, all micropatterns in this study were obtained following the LIMAP protocol 16 using a UV-projector in a fluorescence microscope and the photosensitizer 4-benzoylbenzyl)trimethylammonium bromide (BBTB), see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This led to breakthroughs in biology, allowing researchers, for example, to print cell adhesion proteins to constrain cell shape and thus reveal the physical basis of cell polarity 4 and spindle orientation during mitosis in cultured cells 5 . Concomitantly, the ability to print purified proteins onto glass brought better control in in vitro reconstitution studies, which strengthened our understanding of the dynamics of cytoskeleton contractility 6 , as well as the physiology of cytoskeletal polymers 7,8 . Finally, it was recently demonstrated that electron microscopy grids could be micropatterned with cell adhesion molecules 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…These and other studies have led to the growing appreciation that lattice dynamics of even stable microtubules can provide access to luminal residues along the shaft of microtubule polymers. Recently, Schaedel et al, reported a passive breathing mechanism for microtubules in which α/β tubulin dimers can be evicted and replaced from the microtubule shaft via an energy consuming process 16 . SWI/SNF complexes are known to evict histones and other proteins from nucleosomes during chromatin remodeling [17][18][19] , suggesting the intriguing hypothesis that PBAF, and perhaps other SWI/SNF complexes, could be playing a similar role in evicting tubulin and/or other microtubule associated proteins during microtubule remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…The pellet was removed and supernatants collected as whole cell extract for immunoblotting and immunoprecipitation analysis for soluble proteins. For subcellular fractionation, the pellet was collected after centrifugation as above, and resuspended in a hypotonic buffer (10 mM HEPES, pH 7.2, 10 mM KCl, 1.5 mM MgCl2, 0.1 mM EGTA, 20 mM NaF, and 100 μM Na3VO4), and disrupted using a manual homogenizer for [15][16][17][18][19][20] times. Disruption of the cells was confirmed using a hemacytometer.…”
Section: Whole Cell Lysis and Sub-cellular Fractionationmentioning
confidence: 99%